Exploring ICU Nurses Knowledge, Attitude, and Self-Efficacy in Delivering Palliative Care: A Scoping Review - Lurdes Acorta Freitas; Hartiah Haroen; Ayu Pawesti Priambodo (Universitas Malahayati, 2026)
ABSTRACT The integration of palliative care into intensive care units (ICUs) is increasingly recognized as vital in addressing the complex needs of critically ill patients. Nurses in ICUs play a key role in ensuring quality palliative care. However, disparities in knowledge, attitudes, and self-efficacy among ICU nurses remain barriers to optimal care delivery. This scoping review aimed to systematically explore the current evidence on ICU nurses’ knowledge, attitudes, and self-efficacy in delivering palliative care. A scoping review following PRISMA-ScR guidelines was conducted. Literature was systematically searched from CINAHL, PubMed, Scopus, Taylor Francis, and Google Scholar using keyword combinations mapped with MeSH terms. A total of 11 eligible articles were included after applying predefined PCC (Population–Concept–Context) criteria. Quality appraisal was conducted using the JBI checklist. Data were analyzed descriptively qualitatively. 11 studies were analyzed in this review. The findings revealed that most ICU nurses had insufficient knowledge of palliative care, particularly in psychosocial and spiritual dimensions. Attitudes towards palliative care were mixed; while some studies reported favorable views, others indicated high rates of ambivalence or negativity. Self-efficacy levels also varied, though studies showed it was generally higher among nurses with formal training or greater experience. ICU nurses’ knowledge and attitudes significantly influence their confidence and ability to deliver effective palliative care. Despite moderate self-efficacy reported in some regions, widespread gaps in knowledge and inconsistent attitudes underscore the urgent need for targeted education, policy support, and ongoing competency development. Keywords: Palliative Care, Intensive Care Unit, Nurses, Knowledge, Attitudes, Self-Efficacy.